CHEMICAL PERSPECTIVES ON THE IMPACT OF CLIMATE CHANGE IN AFGHANISTAN: A COMPREHENSIVE REVIEW - Khan, Zardar; Bawari, Noorzaman; Wadeer , Shukrullah; Niazi, Mohammad Jawad; Nazar, Nazar Mohammad; Aftab, Safir Ullah (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
: Climate change is a global phenomenon that has significant impacts on various aspects of human life, including the environment, economy, and social well-being. Afghanistan, one of the least developed and most vulnerable countries to climate change, is facing alarming effects due to its high dependence on agricultural livelihoods, fragile environment, poor socio-economic development, high frequency of natural hazards, and over four decades of conflict. This comprehensive review aims to provide an overview of the current state of knowledge on the impact of climate change on Afghanistan's environment, economy, and society, and to highlight the vulnerability of Afghanistan to climate change. The review also explores the chemical composition of air pollutants in Afghan cities, the impact of air and water pollution on human health and the environment, the influence of climate change on soil composition and nutrient availability, and the implications for water resources, including groundwater quality and availability. Finally, the review discusses the chemical aspects of climate change adaptation and mitigation efforts in Afghanistan, focusing on innovative technologies and practices to address climate-related challenges in the country.